Acute Abdominal Compartment Syndrome following Extraperitoneal Bladder Perforation - Ana Licina (Case Reports in Anesthesiology)
Extraperitoneal bladder perforation is a known complication of a commonly performed rigid cystoscopy. If unrecognized, this complication can lead to continuous intra-abdominal fluid leakage with consequent organ function impairment and symptoms. This is the first case report in literature of a transurethral bladder perforation causing an acute abdominal compartment syndrome, which was subsequently managed conservatively with supportive management only. Case Presentation. We describe a clinical course of a 73-year-old Caucasian female whose initial acute presentation involved urinary symptoms. Surgery and general anaesthesia during rigid cystoscopy were complicated by an initially unrecognized extraperitoneal bladder perforation, resulting in fluid extravasation. This extravasation resulted in transurethral bladder resection syndrome with acute intra-abdominal free fluid accumulation. This complication caused acute abdominal compartment syndrome resulting in respiratory end-organ compromise and immediate postextubation respiratory failure. Patient required an emergency reintubation. During the management, diagnosis was considered through the use of the point of care abdominal ultrasound. Postoperatively, patient was managed conservatively in intensive care. Postoperative course included an approximate nine liters of urinary diuresis and supportive ventilation for four days. Conclusion. There is equipoise in the clinical management of abdominal compartment syndrome with regard to supportive medical management alone or invasive surgical treatment.